The Effects of EU Migration Policies on The Labor Market - Mammadov, Ilkin; Çak, Demet (International Journal of Economics and Financial Issues, 2025)
The impact of migration policy on the labour market in the European Union has increased significantly in recent years. The causes of international migration have become more complex, varying with political, economic and social changes. In particular, the influx of non-EU nationals from the Middle East and North Africa has created inequalities in the level of participation in the European labour market. Although EU policy has been shaped by a balance between security and labour needs, encouraging temporary and cyclical migration, the level of participation of non-EU nationals in the labour market remains low. Statistical data show that long-term unemployment and youth unemployment rates are also higher in this group. Gender and skills gaps also weaken the possibilities of labour market integration. Despite integration measures and legal reforms, structural barriers, stigmatisation and discrimination deepen inequalities in the labour market. Therefore, more effective social inclusion and labour market strategies are needed.